Analysis of Korean journals rejected by Scopus since 2011 - Hyunju Jang (Science Editing, 2020)
This paper aims to provide publishers and societies who plan to apply for their journals to be listed in Scopus with critical guidelines to evaluate their performance from an objective, globally-informed perspective. It presents a qualitative case study of how applications of Korean journals to Scopus have been evaluated over a 9-year period (2011–2019). A content analysis was conducted of 106 applications that were rejected by the Content Selection and Advisory Board, according to a combination of 14 quantitative and qualitative selection criteria. This case study was used to categorize instances of failure and to illustrate practical strategies for local journals to use when applying to Scopus based on the lessons to be learned from rejected cases. The results of the analysis show that local journals should enhance the quality of the articles they publish, review why the journal should be considered international, and clearly address editorial policies and the concept, scope, and strategies of the journal.